Akibat Hukum Atas Penyalahgunaan Hak Kekebalan DiplomatikDitinjau Dari Konvensi Wina 1961(Studi Kasus Penyeludupan Emas Yang Dilakukan Oleh Pejabat DiplomatikKorea Utara Di Bangladesh) - Nyoman Tia Resita Dewi; Dewa Gede Sudika Mangku; I Wayan Lasmawan (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2020)
This study aims to determine and analyze the rights of immunity and privileges held by diplomatic representatives under the1961 Vienna Convention and analyze the legal consequences of the abuse of immunity rights and diplomatic privileges ingold smuggling cases carried out by North Korean diplomatic representatives in Bangladesh. This type of research is anormative type of research, the approach in research is the statute approach, case approach, and conceptual approach.Sources of legal materials used are primary, secondary and tertiary legal materials. Legal material collection techniquesused by argumentation techniques and discussed descriptively. The results of this study show that (1) North Koreandiplomatic representatives in Bangladesh also have the rights of immunity and privileges as determined in the 1961 ViennaConvention, (2) the legal consequences of abuse of the right of immunity related to diplomatic bags for Bangladesh as acountry recipients namely under Bangladesh law, North Korean diplomatic representatives may be sentenced to death, lifeimprisonment and be fined, but North Korean diplomatic representatives have immunity that cannot be meted out. As for thelegal consequences for North Korea as a sending country, namely Bangladesh as a recipient country, namely Bangladesh canconduct non-grata persona on North Korean diplomatic representation if the immune rights have been carried out by NorthKorea